Quasiconformal Harmonic Mappings Related To Starlike Functions - Yavuz Duman, Emel; Kahramaner, Yasemin; Aydoğan, Melike; POLATOĞLU, YAŞAR (Eudoxus Press, Llc, 1424 Beaver Trail Drive, Cordova, Tn 38016 Usa, 2014)
Let f = h(z) + <(g(z))over bar> be a univalent sense-preserving harmonic mapping of the unit disc D = {z is an element of C parallel to z vertical bar < 1}. If f satisfies the condition vertical bar w(z)vertical bar = vertical bar g'(z)/h'(z)vertical bar < k, (0 <= k < 1), then f is called k-quasiconformal harmonic mapping in D. The aim of this paper is to investigate a subclass of k-quasiconformal harmonic mappings.
Keywords: k- quasiconformal harmonic mappings; distortion theorem; coefficient inequality